2017
DOI: 10.1007/s10571-017-0511-3
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Response to Stressors in Newly Diagnosed Patients with Multiple Sclerosis

Abstract: Autonomic dysfunction is commonly detected in patients with multiple sclerosis (MS). However, data evaluating autonomic nervous system function in early MS are limited. Present study investigates response to two different stressors in newly diagnosed MS patients, looking for the signs of autonomic dysfunction at the beginning of the disease. We examined 19 MS patients and 19 age, sex, and body mass index matched healthy controls. MS patients were newly diagnosed, untreated, and with low expanded disability sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This conclusion is reinforced when the results of studies that required verbal responses in the Stroop test were compared to studies where no verbal responses were necessary. A significant decrease in HF (ms 2 ) in response to the Stroop test was, for instance, found in previous studies where the participants did not have to report their responses verbally [63, 67, 68], while a lack of any statistically significant change in HF (ms 2 ) was found in the study by Garafova et al [69] that required participants to verbally report their responses. Therefore, both RMSSD and HF (ms 2 ) do appear to be able to index the activity of the PSNS; however, when a study task may induce substantial respiratory changes, then both variables should be included as markers of parasympathetic activity.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This conclusion is reinforced when the results of studies that required verbal responses in the Stroop test were compared to studies where no verbal responses were necessary. A significant decrease in HF (ms 2 ) in response to the Stroop test was, for instance, found in previous studies where the participants did not have to report their responses verbally [63, 67, 68], while a lack of any statistically significant change in HF (ms 2 ) was found in the study by Garafova et al [69] that required participants to verbally report their responses. Therefore, both RMSSD and HF (ms 2 ) do appear to be able to index the activity of the PSNS; however, when a study task may induce substantial respiratory changes, then both variables should be included as markers of parasympathetic activity.…”
Section: Discussionsupporting
confidence: 54%
“…With regard to the absolute units of LF, a small number of studies have reported a significant increase in LF (ms 2 ) in response to orthostatic stress [62, 66, 76]. However, many studies found no statistically significant change [57, 64, 65, 79, 83, 84] and some even found a decrease in LF, when expressed in absolute units, in response to orthostatic stress [58, 60, 63, 85]. Our results appear to agree with the majority of findings where significant increases in LF (nu) were found in response to both stressors, and no statistically significant change in LF (ms 2 ) in response to either stressor was observed (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is good evidence that CAD is worse in patients with progressive MS than in RRMS [45,46,81]. CAD appears to worsen with longer disease duration, although it may be present at diagnosis and worsen soon thereafter [41,49,[51][52][53]. There is also some evidence for an association with EDSS and disease activity [5,43,76,82].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study showed that HRV was already decreased in 51 patients with newly diagnosed RRMS compared with 44 age-and sex-matched controls [50]. On the other hand, a slightly diminished sympathetic response to a mental stress test, but unchanged response to orthostasis, was seen in 19 newly diagnosed untreated MS patients compared with 19 age-, sex-and body mass index-matched controls [51]. In the 1990s, one study in 46 MS patients (20 RRMS,26 SPMS) found that orthostatic HR response showed significant worsening over 1 year [52], while another reported worsening of HRV on deep breathing and immediate orthostatic HR response over 2 years in 20 RRMS patients [53].…”
Section: Association With Ms Type and Disease Characteristicsmentioning
confidence: 97%
“…Another possibility is that patients showed a blunted cardiovascular response as an indicator of disruption in adaptive processes. In fact, a diminished sympathetic response to a mental stress test has been found in multiple sclerosis patients (Vlcek et al, 2018). Moreover, this sympathetic response to stressors can be associated with activity and connectivity brain systems (Ginty et al, 2017), suggesting that miscalibration in cardiovascular activity and neural networks can be interactive.…”
Section: Discussionmentioning
confidence: 99%